PENETAPAN UANG BELANJA PERNIKAHAN PADA SUKU MELAYU DI DESA TELUK BANO 1 KECAMATAN BANGKO PUSAKO KABUPATEN ROKAN HILIR - Pujiyati "; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Marriage is a very sacred procession for everyone. There are many stages that every couple must go through if they want to get married. One of the stages that will be passed is the Determination of Marriage Spending Money. The determination of the spending money is carried out by the woman's family by considering certain criteria. The purpose of this study was to determine the criteria and implementation of the determination of the wedding spending money on the Malays in Teluk Bano 1 Village. This type of research was a qualitative research with a descriptive approach. The subjects in this study were 12 informants selected using a purposive sampling technique. The results of this study show that there are 6 (six) criteria in determining the amount of money for wedding expenses in the Malays, such as the background of the prospective son-in-law, children's education, family economy, children's beauty, religion in the family, and children's work. Implementation of the determination involves both parties, and before reaching an agreement there is a bargaining process. The hope is that when determining the amount of money for family weddings, the woman is able to match the criteria with the man, it is preferable to involve a third party in the implementation such as the local village customary holder. Key words: Marriage Spending Money, Malay Tribe, Determination, Criteria, Implementation.